Analysis of the Technological Feasibility of the Biodiesel Production Chain in the State of Ceará - Carmo, Breno Barros Telles do; Albertin, Marcos Ronaldo; Dutra, Nadja Glheuca Silva; Rodrigues, Maxweel Veras (Revista Gestão da Produção Operações e Sistemas, 2008)
The purpose of this study is to investigate the technological structure of the biodiesel productive chain (CPB) in Ceará. The objective is, initially, to map the demands and technological offers of products, processes and management, identifying opportunities and challenges for regional development. The survey of information from this exploratory and descriptive study occurred through technical visits, literature, participation in seminars and conferences, and interviews with entrepreneurs and researchers. The major technology gaps and opportunities were identified for each link of the CPB, from the process of planting and managing the product and its crushing to the refinement of the biodiesel. The greatest needs encountered included, the need for technological management in companies that manufacture equipment, lack of agribusiness skills and in the associations of family farming to manage the micro power plant crushing and refinement, technologies to add value and apply co-products as well as the lack of mamona as a raw material. Overcoming these technology gaps will contribute to the sustainable development of CPB, mitigating the environmental and socioeconomic problems of the State and promoting economic inclusion of thousands of families in the semi-arid northeast. Keywords: Productive chain. Biodiesel. Demands and Technological Offers